PERAN PESANTREN ZAD INTERNATIONAL QUR’ANIC BOARDING SCHOOL DALAM MENGHADAPI ERA GLOBALISASI - Latipah, Euis (Dirasa Islamiyya: Journal of Islamic Studies, 2023)
One of the characteristics of the era of globalization is the rapid science of science and technology. Pesantren is one of the Islamic educational institutions that must be able to answer the challenges in the era of globalization. The purpose of this study is to describe the role of pesantren in facing the era of globalization. This research uses qualitative research methods with a case study approach. Research location at Pondok Pesantren Zad Insaniyah Cianjur Data collection techniques using; observations, interviews, and documentation. The results of this study show that pesantren has a role in facing the era of globalization with the development program of Arabic and English as an international language, the combination of the diknas curriculum with the pesantren curriculum, the development of talent and interests of students, the existence of educational work with Saudi Arabia. With the hope of becoming a human being who mastered science either religious science or general science by having a strong character and having a strong character.